Polycystic ovary syndrome and Hashimoto’s thyroiditis: An autoimmune relationship - Önmez, Attila; Gökosmanoğlu, Feyzi; Aksoy, Erkan (Journal of Surgery and Medicine, 2019)
Aim: Polycystic ovary syndrome (PCOS) and Hashimoto’s thyroiditis (HT) are common and frequently comorbid diseases. A genetic predisposition and an inflammatory and autoimmune relationship have been posited between them. This study examines the role played by autoimmunity in the relation between PCOS and HT. Methods: This case-control study was conducted at the Medical Park Hospital endocrinology and gynecology departments, Ordu, Turkey, from July 2015 to December 2018. Reproductive-age women diagnosed with PCOS based on the Rotterdam criteria, women diagnosed with HT, and healthy women with neither PCOS nor HT were included in the study. Thyroid function tests, thyroid autoantibodies, gonadotropins, androgen hormones, fasting glucose and insulin levels, and body mass index (BMI) were compared among the three groups. All patients also underwent pelvic and thyroid ultrasound examinations. Results: Five hundred ninety-six women were included in the study, 254 in the PCOS group, 190 in the HT group, and 152 in the control group. BMI was significantly higher in the PCOS and HT groups than in the control group (P=0.012, and P=0.027, respectively). Menstrual and androgenic symptoms were also significantly higher in the patient groups than in the control group (P<0.001). The incidence of TPOAb and TgAb positivity was again significantly higher in the PCOS patients than in the controls (P<0.001). Conclusion: This research demonstrated a higher prevalence of HT, together with elevated TSH, anti-TPO, and anti-Tg levels in PCOS patients. Our data suggest that thyroid functions and ovaries should be screened later in life in patients with PCOS and HT.